Modern Slavery in Fishing Industry: the Need to Strengthen Law Enforcement and International Cooperation - Aryuni Yuliantiningsih; Jaco Barkhuizen (Faculty of Law, Universitas Sebelas Maret, 2021)
The global fishing industry supports the livelihoods of millions, however, it adversely allows the occurrence of crimes throughout the value chain, especially modern slavery. This research aims to examine the current existence of slavery in the fishing industry for the state to determine the best way to deal with its repeated occurrence. Studies show that slavery still exists due to the vulnerability of the fishing sector. These include the prolonged timeframe onboard which prevents the crew from leaving the vessel, poor working conditions, the long-hours associated with the catching process, lack of access to authorities, use of foreign flags to create barriers to the law enforcement, use of migrant labour lacking representation and the lack of governmental oversight or support. This research states that it is important to combat modern slavery by strengthening law enforcement, policy, and international cooperation between States, by involving the source, flag, coastal, port, trade and market States based on international and national law